2011
DOI: 10.1093/cercor/bhr052
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Memory for Intentions: A cTBS Investigation of the Frontopolar Cortex

Abstract: The present study aimed to investigate the role of frontopolar cortex in prospective memory (PM) by means of inhibitory theta-burst stimulation (cTBS). "Experiment 1"-8 volunteers were evaluated after inhibitory cTBS over left Brodmann area (BA) 10, right BA10, and Cz. In the PM procedure, sequences of 4 words each were presented. During the intersequence delay, subjects had to repeat the sequence in the observed order (ongoing task forward) or in the reverse order (backward). At the occurrence of a target wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 43 publications
4
23
1
Order By: Relevance
“…An initial sample size of 16 was chosen based on two studies using a very similar cTBS design that stimulated lateral FPC (Costa et al, 2011;Costa et al, 2013) and this was augmented to 31 on the basis of feedback from reviewers. Five participants (5 female, 0 male) were excluded from the analysis due to chancelevel performance in both experimental sessions.…”
Section: Methodsmentioning
confidence: 99%
“…An initial sample size of 16 was chosen based on two studies using a very similar cTBS design that stimulated lateral FPC (Costa et al, 2011;Costa et al, 2013) and this was augmented to 31 on the basis of feedback from reviewers. Five participants (5 female, 0 male) were excluded from the analysis due to chancelevel performance in both experimental sessions.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to integrating complex relationships and representing complex rules, the rostral PFC is involved in prospective memory (Burgess, Scott, & Frith, 2003;Costa et al, 2011;Reynolds, West, & Braver, 2009;Volle, Gonen-Yaacovi, de Lacy Costello, Gilbert, & Burgess, 2011). Prospective memory plays an important role in our experimental design because instructions are encoded at the beginning of a trial but executed only at a later time (Fig.…”
Section: Present Limitationsmentioning
confidence: 99%
“…It should be noted, however, that in two recent studies of healthy subjects in which the role of the frontal pole in PM functioning was investigated using transcranial magnetic stimulation, the authors found differential left versus right involvement as a function of the material employed in the PM procedure (i.e., words versus spatial location, resp.) [41, 50]. …”
Section: Discussionmentioning
confidence: 99%
“…The experimental procedure was a slightly modified version of a procedure we used in two previous studies [41, 42]. The experimental material consisted of 54 bisyllabic words, all of which were used for the ongoing task; a subset of 10 (out of 54) words constituted the PM target stimuli.…”
Section: Case Reportsmentioning
confidence: 99%